Dichotomous Contingent Valuation of three ecosystem services of the Chimborazo Fauna Production Reserve, Ecuador (Agroindustrial Science, 2024)
The moorland or paramo is a threatened ecosystem. The indiscriminate advance of the agricultural frontier is producing the loss of ecosystem services, especially water service. This research estimated the willingness to pay (WTP) of the water users corresponding to the Municipality of Riobamba for the conservation of 3 ecosystem services: water service, soil conservation and scenic beauty of the Chimborazo Fauna Production Reserve (RPFCH). Four hundred and six surveys were applied by means of the double limit dichotomous contingent valuation method, using a maximum likelihood model in the Stata software. Four models were developed: simple limit, simple limit with other explanatory variables, double limit, and double limit with other explanatory variables, the latter being statistically more significant. As a result, it was determined that the WTP for the ecosystem service of water production is USD 0.84, for soil conservation USD 0.88 and for scenic beauty USD 0.81 per month that they would be willing to pay for the care of these services.
Keywords: Contingent valuation; Dichotomous Model; Moorland; Water Economy